Analisis Hasil Evaluasi Siswa terhadap Desain Pesan E-Modul IPA Berbasis Projek pada Materi Pencemaran DI SMP NEGERI 19 KOTA PONTIANAK - Wahab, Rahmawati; Ariyati, Eka (FKIP Universitas Tanjungpura, 2026)
This study explores students' evaluations of message design within a project-based e-module in science education, specifically on the topic of environmental pollution at SMP Negeri 19 Kota Pontianak. The integration of digital technology in learning, including the use of interactive and structured e-modules, is expected to improve student engagement and understanding. This descriptive quantitative research involved 136 students who evaluated four key aspects of message design: clarity, alignment with learning objectives and student characteristics, visual presentation and navigation, and interactivity. Findings show that the e-module was well-received, with message clarity and visual-navigational elements rated most highly. Meanwhile, content alignment and interactivity, while still positive, indicated room for improvement. These results affirm the importance of effective instructional message design in digital learning environments. It is recommended that future development efforts maintain the clarity and visual appeal of the module while enhancing differentiation and interactivity to better meet diverse student needs